Local Food Halal Guarantee: Implementation of Halal Slaughterer Training (JULEHA) in Pekalongan Regency - Adinugraha, Hendri Hermawan; Sholehuddin , M. Sugeng; Kusuma Dewi , Anggun Rahadian; Farmawati, Ira; Andrean , Rizky (Dharmahita: Journal of Community Service and Development, 2025)
The implementation of halal certification for animal-based food products at the local level is greatly influenced by the competence of Halal Slaughterers (JULEHA). This community service research aims to improve the understanding, skills, and awareness of slaughterers regarding the importance of slaughtering by Islamic law and national regulations. The implementation method employed a two-day approach combining socialization, education, and participatory seminars, involving 50 participants from three sub-districts in Pekalongan Regency. Pre-test results indicated that 74% of participants had low levels of understanding. Following training, 68% achieved high levels of experience, with an average score increase of 33.9 points. Observation results showed that over 85% of participants were able to apply halal slaughtering techniques correctly. The evaluation also revealed that 92% of participants were motivated to pursue formal halal certification. In conclusion, this training effectively enhanced the competencies of local slaughterers and fostered a community-based halal food ecosystem. Further recommendations include replicating the program in other regions and providing ongoing capacity building through strategic cross-institutional partnerships.